PEMANFAATAN ZEOLIT NAA DARI KAOLIN SEBAGAI ADSORBEN LOGAM BESI (FE) PADA LIMBAH CAIR LABORATORIUM - Zuryati, Ulul Khairi; Honiar, Ruru; Fahrurazi, Fahrurazi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Excessive iron (Fe) content in water caused corrosion and at high amounts are toxic to the human body. One of the laboratory waste water treatment techniques is adsorption method. The adsorbent used in this study was zeolite NaA which was synthesized using kaolin as one of the most abundant minerals in Indonesia. The zeolite obtained was analyzed by FTIR to determine the functional groups. The synthesis of NaA zeolite have been successful indicated by the absorption band appeared in the wavenumber range of 558–546 cm−1 which showed the formation of double ring structure as a characteristic of the NaA zeolite crystal. Optimum pH for adsorption of Fe (II), Fe (III) ions and mixtures in laboratory waste using zeolite NaA is 3. The maximum adsorption capacity of NaA zeolite on Fe (II), Fe (III) ions and laboratory wastewater are 16.00, 18.33, and 6.50 m/g adsorbent. Whereas adsorption equilibrium times for Fe (II), Fe (II), and laboratory deposit waste water were 30, 20, and 10 minutes, respectively.